AVAILABILITY LISTING SYSTEM ELECTRONIC GOODS IN PT. PRIMABUANA USING MICROSOFT VISUAL BASIC 6.0 - Khairunnisa Khairunnisa; Don Elsyafitra, SKom Don Elsyafitra, SKom (Jurnal Sistem Informasi, 2007)
This writing explains the electronic inventory recording system on PT. Primabuanathat during this process is still using a manual system, so many possibilities of errors.Therefore, the authors provide a better alternative to create a computerized inventorysystem using Visual Basic 6.0 programming language, the authors propose to assistthe process of data processing to make report.